Long COVID-19: Multidisciplinary Approach and Pulmonary Fibrosis Sequelae - Febrina, Nidya; Yovi, Indra (Indonesian Society of Respirology (ISR), 2024)
COVID-19 patients may experience a persistent condition of post-COVID-19 infection, which is known as the long-COVID phenomenon or post-acute sequelae of SARS-CoV-2 infection (PASC) or post-acute COVID-19 syndrome (PACS) with long-term sequelae characteristics that stay after the convalescent period of COVID-19 disease. The most common clinical symptoms found within 5 weeks post-infection were fatigue (12.7%), cough (12.4%), headache (11.1%), loss of sense of taste or smell (10.4%), and muscle pain (8.8%). Women have a slightly higher prevalence than men, with a value of 23.6% and 20.7%, respectively, which are dominated by 35-49 years old (26.8%), 50-69 years old (26.1%), and 25-34 years old (24.9%). Pulmonary fibrosis sequelae in COVID-19 occur due to the destruction of the alveolar epithelium and the formation of active myofibroblast foci, causing excessive accumulation of extracellular matrix in lung tissue. Long COVID management requires a multidisciplinary approach, including health workers and the wider community, as well as systematic assessment management. The recommended therapy includes pharmacological (symptomatic, micronutrients, antibiotics, and anti-inflammatory) and non-pharmacological (medical and psychosocial rehabilitation). This review aims to summarize the long COVID and multidisciplinary approach to improve the patient's quality of life.